Role of Economic Factors in Promoting Dalit Education - Lamsal, Gopal; Maharjan, Ram Krishna (Journal of Advanced Academic Research, 2017)
The study was conducted to identify the Role of economic factors in promoting Dalit Education. Dalits are socially, educationally, politically and economically backward. Dalits are known as the disadvantage communities who are culturally categorized as the untouchable caste in society. Legally, it is not allowed to do discrimination in spear of social activities on the basis of caste and ethnicity even though it is still in practice. The study was conducted among the 227 Dalit students, 18 guardians and 25 key informant interview group was in-depth interview and discussion in Nawalparasi district of Nepal. Purposive sampling technique was used to select the respondents from the Dalit communities. School enrolled children were participated in this study. Self-reported structured questionnaire was formed in 5 point Likert's scale to collect the perceptual data. Grade wise, mainly grade 5-10 students at least sometimes felt the problem of tiffin money, problem to manage the expenditure of their school's stationeries, problem of one uniform, feeling of sadness when they had no shoes like other friends, feeling of stress when they could not pay the school's fee and problem of one uniform. In all these issues there was highly significant association (p = .000) found on perception of different grade Dalit students. From the discussion, it was found that the Role of economic factors in promoting Dalit Education.